2005
DOI: 10.1074/jbc.m409791200
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc Inhibit Gαs Function

Abstract: ؊ with the nucleotide-free G␣ s is sufficient to activate AC. Using antibodies to the N and C termini of G␣ s , we show that the Cu 2؉ interaction site on the G protein is in the C terminus. We conclude that Cu 2؉ and Zn 2؉ generate a nucleotide-free state of G␣ s and that, in the absence of any nucleotide, the ␥-phosphate mimic of GTP, AlF 4 ؊ , alters G␣ s structure sufficiently to permit stimulation of AC activity. Moreover, our finding that isoproterenolstimulated AC activity was more sensitive to inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Gene sets associated with di-valent ions, ion channels and g-proteins were overrepresented at the lowest dose of copper (Cu-L), whereas transport and stimulus response/detection gene sets appeared within the list of significant gene sets at higher concentrations (Supplemental Table 3). These data agree with the closely related abovementioned Top GO term analysis, and suggest an initial disruption of ion homeostasis within the olfactory tissue, possibly by preventing the closing of important ion channels, followed closely by inhibition of g-protein function (29,30). Several gene sets related to the regenerative properties of the olfactory system were present within the significant gene sets at Cu-L and Cu-H (Figure 2, dashed arrows).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Gene sets associated with di-valent ions, ion channels and g-proteins were overrepresented at the lowest dose of copper (Cu-L), whereas transport and stimulus response/detection gene sets appeared within the list of significant gene sets at higher concentrations (Supplemental Table 3). These data agree with the closely related abovementioned Top GO term analysis, and suggest an initial disruption of ion homeostasis within the olfactory tissue, possibly by preventing the closing of important ion channels, followed closely by inhibition of g-protein function (29,30). Several gene sets related to the regenerative properties of the olfactory system were present within the significant gene sets at Cu-L and Cu-H (Figure 2, dashed arrows).…”
Section: Resultssupporting
confidence: 90%
“…Studies using mammalian epithelial cells of olfactory tissue have shown that exposure to copper and zinc prevent the closing of divalent ion channels leading to excessive neuronal excitability (26,27). Metals can also alter olfactory sensitivity, GTP-binding proteins, and block cyclic-nucleotide-gated channels (28-30), suggesting that there are multiple molecular targets in the olfactory system which may be impaired by metal exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby the whole cascade of LPS-induced NFκB signaling pathway is suppressed [ 133 ]. Cyclic nucleotides are not only affected by zinc flux, but the homeostatic zinc signal has been shown to inhibit AC, causing decreased cAMP levels, while GC activity and cGMP levels are not affected [ 134 , 135 ]. Increased cAMP and cGMP levels have been associated with monopoiesis, which will be discussed later.…”
Section: Zinc Signaling and Immunitymentioning
confidence: 99%
“…Toxic doses of zinc inhibit intestinal alkaline phosphatase [22], mitochondrial cytochrome c oxidase [23], glyceraldehyde-3-phosphate dehydrogenase [24], beta amylase [25]. Furthermore Zn 2þ decrease steady-state GTPase activity by inhibiting the binding of GTP to Galpha(s) and also, toxic doses modify excretion of nitrogen, phosphorus, and sulfur [26]. Zinc ion has been found to be a powerful competitive inhibitor of G-6-PD from Aspergillus parasiticus.…”
Section: Introductionmentioning
confidence: 99%